Consulting the South African experts in physiotherapeutic stroke rehabilitation - L. A. Hale; C. J. Eales (AOSIS, 2001)
This paper presents the opinions of expert physiotherapists on what constitutes optimal stroke rehabilitation in South Africa. Data were collected by the use of the Delphi technique. Consensus was reached after two rounds, and the respondents' views are summarised and discussed within the framework of South African health care. Results showed that physiotherapy was felt to be very important after stroke, and the survey created a profile of the skills that physiotherapists may require in order to work in this field. However, no new or innovative methods by which appropriate rehabilitation services could be delivered in South Africa were generated by the survey. The Delphi technique is described and its use in this survey considered.